PROBLEMATIKA MENULIS TEKS DESKRIPSI DI SMP NEGERI 8 KOTA SERANG - Diwansyah, Fitria Anggraini; Muhyidin, Asep (Jurnal Membaca Bahasa dan Sastra Indonesia, 2025)
This study aims to identify and analyze the problems faced by students in writing description texts at SMP Negeri 8 Kota Serang. Writing descriptive texts is an important skill that requires mastery of vocabulary, understanding of text structure, and the ability to compose cohesive and coherent sentences. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and questionnaire analysis. The subjects of the study were students of grade VII-J SMP Negeri 8 Kota Serang and Indonesian teachers of SMP Negeri 8 Kota Serang. The results of the study show that the main problems faced by students include low vocabulary mastery, difficulty understanding the structure of descriptive texts, and lack of motivation in writing. In addition, conventional teaching methods and the lack of use of innovative learning media are also inhibiting factors. This study recommends the use of relevant learning media, such as pictures, videos, or interactive applications, to increase student’s interest. Teachers are also expected to develop more creative teaching methods and provide clear guidance in writing descriptive texts. Thus, it is hoped that the problems faced by students can be minimized and the ability to write descriptive texts can be significantly improved.